Diffability And Hope Reflected In Sean Mcnamara's Soul Surfer Movie (2011): An Individual Psychological Approach - Rahmatin, Putri Nilam; , Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed; , Drs. H. Abdillah Nugroho, M. Hum (2013)
The major problem of this study is to reveal how Bethany's abnormality to keep her hope become true in Soul Surfer movie. The objective of this study is to analyze the movie based on its structural elements and an individual psychological approach. In analysis, the writer uses descriptive qualitative method. The object of this study is Soul Surfer directed by Sean McNamara. The data sorces are primary and secondary data sources. The primary data source is Soul Surfer movie itself and the secondary data sources are the other sources related to the primary data such as informations about director's biography, websites, and the other sources such a book related to the analysis. The technique of the data collection are watching the movie repeatedly, taking note the important part, arranging the data into several groups, selecting particular parts that is important and relevant for analysis, drawing conclusion, educational implication, and formulate it's suggestion. The technique of data analysis is descriptive analysis. The result of this study is presented in the following conclusions. First, Sean McNamara wants to describe that nothing is impossible in the world if human wants to believe, try hard, and do the best. He wants to show that lack or abnormality is not something that can limit people to achieve their hope. Love of God and lovely people is the most powerful thing to raise the dream. Second, based on individual psychological analysis, Sean McNamara wants to deliver optimism of Bethany Hamilton in her striving to achieve her hope with an abnormal condition.